Fixed-Term Employment and Fertility: Evidence from German Micro Data - Wolfgang Auer; Natalia Danzer (Institute for the Study of Labor (IZA), 2014)
We study the short- to medium-run effects of starting a career on a fixed-term contract on subsequent fertility outcomes. We focus on the career start since we expect that temporary contracts and their inherent economic uncertainty imply a path dependency which might have spill-over effects on other domains of life. Our empirical analysis is based on rich data from the German Socio-Economic Panel which provides comprehensive information about individuals' labour market history as well as fertility behaviour. Our main results are: Women (i) tend to postpone their first birth due to fixed-term employment at labour market entry and (ii) reduce the number of children in the first 10 years after graduation. These associations are strongest in the subsample of native women with at least vocational training. (iii) In contrast, we find no significant correlations for men. We argue that these findings are robust to potential endogeneity threats.
Keywords: J13; J18; J41; 330; career start; fixed-term employment; postponement of maternity; fertility; economic uncertainty; graduation